Evaluación de 2 niveles de inclusión de la zanahoria amarilla (daucus carota) en la alimentación de pollos de engorde - Zuñiga Andrango, Emiliana Patricia (2023)
The objective of this research was to evaluate at two levels of yellow carrot (Daucus carota) inclusion in broiler chickens feed. Present work, 90 broiler units were randomly distributed in three groups with six replications where three treatments with carrot inclusion were applied as follows: T0 (Commercial feed: control treatment), T1 (Commercial feed + 5 % inclusion of carrot) and T2 (Commercial feed + 10 % inclusion of carrot) in a period of six weeks in Selva Alegre neighborhood, Sangolquí parish belonging to the Rumiñahui canton, Pichincha province. As for the methodology, a physical-chemical characterization of the carrot was carried out from carrot peel to describe its properties and composition, then a record was taken of different productive variables such as weight, feed consumption, gain weight, feed conversion, pigmentation level and cost benefit for the respective analysis and results interpretation with application of analysis of variance (ADEVA), Duncan's test (with 95% reliability level), DMS colorimetric scale which significant differences between treatments were shown. It was concluded that the variable of skin pigmentation level in broilers of 2 treatment was the most pigmented in comparison to 0 treatment (control treatment), as well as the obtained results in feed consumption with 1130.33 g., and the best benefit/cost ratio was reflected at control treatment (T0) results with a difference of 0.09 cents and 0.17 cents in comparison to treatments T1 and T2, respectively.